2013
DOI: 10.1021/ef4002154
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Organic Matter in Steam Assisted Gravity Drainage Boiler Blow-Down Water

Abstract: Steam assisted gravity drainage (SAGD) boiler blow-down (BBD) water contains high concentrations of dissolved organic matter (DOM) and total dissolved solids (TDS). A detailed understanding of the BBD chemistry, particularly the DOM composition, is important for better management and recycle of this water. In this study, we fractionated the dissolved organic matter in the BBD using DAX-8, Dowex, and Duolite resins into hydrophobic and hydrophilic fractions of acid, base, and neutral compounds. Additionally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 60 publications
2
64
2
Order By: Relevance
“…Increasing hydrophobicity generally leads to more susceptibility to fouling due to the hydrophobic interactions between the membrane surface and the hydrophobic materials [38]. In this study, the organic matter present in the WLS inlet feedwater has been reported to be mainly hydrophobic acids (humic type) [4]. Since all of the membranes tested were hydrophilic (based on the contact angle values in Table 1), it was expected that the membrane surfaces would become hydrophobic after fouling.…”
Section: Continuous Operation At Fixed Phmentioning
confidence: 82%
See 4 more Smart Citations
“…Increasing hydrophobicity generally leads to more susceptibility to fouling due to the hydrophobic interactions between the membrane surface and the hydrophobic materials [38]. In this study, the organic matter present in the WLS inlet feedwater has been reported to be mainly hydrophobic acids (humic type) [4]. Since all of the membranes tested were hydrophilic (based on the contact angle values in Table 1), it was expected that the membrane surfaces would become hydrophobic after fouling.…”
Section: Continuous Operation At Fixed Phmentioning
confidence: 82%
“…), all indicative of the presence of naphthenic acids as the main DOM group in SAGD-produced water. However, Guha Thakurta et al [4] found that the DOM found in SAGD-produced waters are significantly different from OSPW DOM, and more like humic acids than naphthenic acids. It must be noted that every DOM molecule has a specific charge and molecular conformation which controls the rate of fouling and subsequently the performance of the membrane process [25].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
See 3 more Smart Citations